Staying Here, Being There. Bilocation, Empathy and Self-Empathy in Virtual Reality - Pinotti, Andrea (Bollettino Filosofico, 2022)
This paper addresses an ancient desire, attested in several cultures: that of being able to bilocate, to be in two different places, “here” and “there”, at the same time. This desire, which has intercepted the spheres of religious, mystical, esoteric and sci-fi experience, is now being taken up and revived by new immersive virtual reality technologies. By teleporting us (either in the first person or through an avatar) to an “elsewhere”, virtual reality also takes us to other subjectivities, with whom it promises us the possibility of an empathic relationship. Also through a comparison with the medium of film, the paper criticises the dark side of this promise of empathy in VR, deconstructing its rhetoric, and in contrast highlights its bright side and utopian component. Keywords: Avatar, Bilocation, Empathy, Teleporting, Virtual Reality